Implementasi Prinsip Hukum Islam dan Mekanisme Pengawasan terhadap Kepatuhan Syariah pada Lembaga Keuangan Syariah - Anas Anas; Abd. Rahim (Lembaga Yasin AlSys, 2026)
Although the implementation of Islamic legal principles in the practice of Islamic financial institutions (LKS) has attracted scholarly attention, studies that specifically link supervisory mechanisms, particularly the role of the Sharia Supervisory Board (Dewan Pengawas Syariah, DPS) to substantive sharia compliance in the context of limited customer sharia literacy and strong business-oriented pressures remain scarce. This study aims to analyze the implementation of Islamic legal principles and supervisory mechanisms in relation to sharia compliance in LKS. It adopts a qualitative approach with a field research design, involving key informants comprising LKS managers, DPS members, and customers selected through purposive sampling. Data were collected through in-depth interviews, observations, and document studies, and were analyzed through data reduction, data display, and conclusion drawing, using source and method triangulation to ensure the validity of the findings. The results show that the principles of justice, transparency, and the prohibition of riba are implemented through the use of sharia contracts (akad-akad syariah), transparent disclosure of information regarding services and fees, and internal supervisory mechanisms that involve the DPS in document review, product compliance evaluation, and the provision of corrective recommendations. However, sharia compliance has not yet become substantively robust, as it is constrained by limited Islamic economic literacy among some customers and by business orientation pressures that tend to steer compliance toward formal administrative fulfilment. This study contributes to the development of the concept of sharia compliance from the perspective of fikih muamalah and sharia supervisory governance, and deepens understanding of the dynamics of applying Islamic legal values in LKS. The findings underscore the importance of strengthening sharia literacy, enhancing the capacity and independence of DPS, and ensuring consistent sharia compliance audits, while recommending that LKS managers and regulators/stakeholders reinforce customer education, standardize supervisory practices, and mitigate commercial pressures so that they align with the objectives of maslahah (public benefit).